Population structure, gene flow and genetic diversity of sheep blowfly (Lucilia cuprina dorsalis) in Australia - Shilpa Kapoor; Neil D. Young; Aaron R. Jex; Simon Baxter; Ying Ting Yang; Alana J. Davies; Meghan N. Armstrong; Tamara L. Whiteside; Philip Batterham; Robin B. Gasser; Vernon M. Bowles; Trent Perry; et al. (BMC Genomics)
Abstract Background Flystrike (cutaneous myiasis) is caused by blowfly larvae of the genus Lucilia. This disease is a major obstacle to sustainable global sheep and wool production. Flystrike control relies primarily on breech modification surgery (mulesing) and insecticidal treatment; however, control is constantly compromised by the emergence and spread of insecticide-resistance. Preventing the spread of resistance is severely hindered by a limited understanding of genetic variation, structure and gene flow within and among Lucilia populations. Australia is one of the world’s largest producers of sheep and wool products, where Lucilia cuprina dorsalis is the major cause of flystrike. Results Here, we collected 2,034 Lucilia cuprina dorsalis individuals among 86 populations from sheep-grazing regions across the continent. Each fly was genetically characterised at 20,000 loci using DArTseq, a reduced complexity genome sequencing strategy. Three genetically distinct population clusters (i.e., Western Australia, Eastern Australia and Tasmania) were revealed through population structure analyses. Conclusions This investigation into population structure and gene flow yields significant insights into the genetic composition of diverse L. c. dorsalis populations throughout Australia. These findings will be essential for the sustainable management of flystrike on a global scale and for addressing the ongoing challenge of insecticide resistance.